Nation-building and development process - Singh, Lekh Raj (Rawat Publications, 1994)
Papers presented at the National Seminar on "Nation-Building, Development Process, and Communication", jointly organized by the G.B. Pant Social Science Institute, Allahabad and the Centre for Research in Rural and Industrial Development, Chandigarh, 1989.